Upaya Menuju Kelepasan dalam “Geguritan Yadnya ring Kuruksetra” - Ni Putu Parmini (Pusat Kajian Bali Universitas Udayana, 2015)
AbstractThis study analyses the poem titled Geguritan Yadnya ringKuruksetra (The poem on Religious Ritual in Kurusektra)written by Ida Bagus Rai by focusing it on the concept ofrelease (kelepasan), that is the union with God. As a traditionalBalinese literature, this geguritan contains religious valuesand suitable to be applied in the life of an increasinglycomplex and pragmatic situation in the globalization era.In Geguritan Yadnya ring Kuruksetra the author describedthe effort towards deliverance through the implementationof Catur Marga teaching (four-ways) through the charactersof a brahmin family who always bow down and devotionto God, always practice of religious teaching, doing goodand carry out yoga for self-control. The description of effortundertaken by this brahmin family figures reflects theimplementation of elements of Catur Marga that includes thedevotion through pray, knowledge, act, and yoga. Based onthe analysis, this article argues that this geguritan needs tobe promoted widely so that it can be read by more peoplebecause it can deepen their religious knowledge necessary toguide the behavior of doing good.